Precipitation of iron-rich intermetallics and mechanical properties of Al–Si–Mg–Fe alloys with Al–5Ti–B. Issue 17 (22nd November 2018) - Lin, Bo; Li, Haoyu; Xu, Rui; Shi, Ya; Xiao, Huaqiang; Zhang, Weiwen; Liu, Kun
ABSTRACT: Effects of added Al–5Ti–B master alloys on precipitation of iron-rich intermetallics and mechanical properties of A356 cast alloys with high Fe content (1.5 wt-%) were investigated using image analysis, scanning electron microscopy, and tensile testing. Results show that added Al–5Ti–B has apparent refinement on α (Al) grain size of A356 alloys that have high Fe content. 12 wt-% Al–5Ti–B is beneficial for improving mechanical properties of A356 cast alloys with high Fe content. Improved mechanical properties can be attributed to refined microstructure, the proper amounts of TiB2 and Ti(AlSi)3, and decreased porosity. An excessive amount of Al–5Ti–B deteriorates mechanical properties of alloys because it leads to the formation of large secondary intermetallics and increased porosity.